Two new species of the genus Vosmaeropsis Dendy, 1892 (Porifera, Calcarea), with comments on the distribution of V. sericata (Ridley, 1881) along the Southwestern Atlantic Ocean - Cavalcanti, Fernanda F.; Bastos, Nilma; Lanna, Emilio (Zootaxa, 2015)
Two new species of the genus Vosmaeropsis are described: V. recruta sp. nov. and V. complanatispinifera sp. nov., both from the Brazilian coast. These species possess arrow-shaped large diactines in their skeletons, which are being described for the first time in Vosmaeropsis. In addition, the latter species presents another remarkable character: the apical actines of its atrial tetractines is flattened and provided with spines. Vosmaeropsis complanastispinifera sp. nov. is being proposed based on the re-analysis of specimens that in the past were assigned to V. sericata. Thus, with the reallocation of these specimens to the newly described species, the current distribution range of V. sericata does not include the Brazilian northeastern coast. Vosmaeropsis now comprises 23 species. Most of them present an endemic pattern of distribution, but the genus is widely distributed in tropical and temperate regions around the world.